2007
DOI: 10.1007/s00018-007-7368-4
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic effects of Cimicifuga racemosa extract in vivo and in vitro

Abstract: Extracts of Cimicifuga racemosa are used frequently for menopausal complaints. Cimicifuga is well tolerated but can occasionally cause liver injury. To assess hepatotoxicity of cimicifuga in more detail, ethanolic C. racemosa extract was administered orally to rats, and liver sections were analyzed by electron microscopy. Tests for cytotoxicity, mitochondrial toxicity and apoptosis/necrosis were performed using HepG2 cells. Mitochondrial toxicity was studied using isolated rat liver mitochondria. Microvesicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…Such findings are in agreement with those of two recent studies (9,20). However, our findings do not agree with those of a recent animal study stating that C. racemosa exerted hepatotoxicity in vivo and in vitro, eventually resulting in apoptotic cell death in rats (21).…”
supporting
confidence: 45%
“…Such findings are in agreement with those of two recent studies (9,20). However, our findings do not agree with those of a recent animal study stating that C. racemosa exerted hepatotoxicity in vivo and in vitro, eventually resulting in apoptotic cell death in rats (21).…”
supporting
confidence: 45%
“…Therefore, in agreement with the rationale of Lüde et al [14], we considered an evaluation of the hepatotoxicity of C. racemosa in an animal model of estrogen deficiency associated with renovascular hypertension to be necessary. Estrogen deficiency is associated with a higher incidence of hepatic steatosis [15] and both are associated with oxidative stress [4,16].…”
Section: Indroductionmentioning
confidence: 74%
“…Following this rationale and considering the findings of Lüde et al [14], which demonstrated that C. racemosa inhibited mitochondrial b-oxidation and induced steatosis when used at toxic concentrations, we investigated whether the effects of C. racemosa on mitochondrial and peroxisomal b-oxidation were manifested at therapeutic doses in this animal model. Interestingly, different mechanisms appeared to be involved in the b-oxidation responses in the organelles obtained from ovariectomy, hypertension induction, and C. racemosa treatment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations